Islamic religious learning strategy for children and parents of children based on the online platform - Habibah, Lutfiana Nurul; Mustofa, Mahmud Yunus; Yusuf, Achmad; Irsyad, Muhamad Faqih (ATTARBIYAH: Journal of Islamic Culture and Education, 2025)
This study aims to determine the types of teaching materials used in each class program on the Edufic.id online platform. In addition, this study also aims to identify the PAI learning strategies applied and analyze the implications of applying these strategies on students' learning experiences and parental involvement in supporting their children's development. This research uses a qualitative method with a virtual ethnography approach. Data collection techniques obtained by online observation through posting content uploaded by the Edufic.id Instagram account platform. The results of this study indicate that the PAI learning strategy on the Edufic.id online platform is carried out in several ways namely, first, learning strategies by integrating the United Kingdom curriculum with the Islamic curriculum of Al-Azhar, Egypt. Second, the selection of learning methods that are adapted to the characteristics of children’s developmental age (fun-based learning). Third, the use of digital media in learning aims to create a more interactive learning process, and fourth, online-based evaluation strategies that involve parents, so that parents can observe their children’s learning development holistically.